2015
DOI: 10.1080/02701367.2015.1063574
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Accelerometry for Assessing Physical Activity Among Adolescent Girls: Threshold Determination, Validity, Reliability, and Feasibility

Abstract: Purpose Ankle accelerometry allows for 24-hour data collection, improving data volume/integrity versus hip accelerometry. Using Actical ankle accelerometry, the purpose was to (a) develop sensitive/specific thresholds; (b) examine validity/reliability; (c) compare new thresholds with manufacturer’s; and (d) examine feasibility in a community sample (low-income, urban adolescent girls). Methods Two studies were conducted with 6th–7th grade girls (age 10–14 years): Laboratory study (n=24)- Two Actical accelero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Although the hip is the most widely used accelerometer placement site, it is important to explore alternative sites as public health interventions aim to increase wear time compliance and accurate predictions of EE. Previous studies have explored the use of the ankle site in adults (Heil, 2006; Hibbing et al, 2017; Kim et al, 2014; Leenders et al, 2003; Melanson & Freedson, 1995) and youth (de Vries et al, 2011; Hager et al, 2015; Heil, 2006) and have shown conflicting results. de Vries et al (2011), using the ActiGraph accelerometer, showed that the hip, compared to the ankle, was more accurate for predicting PA type using artificial neural networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the hip is the most widely used accelerometer placement site, it is important to explore alternative sites as public health interventions aim to increase wear time compliance and accurate predictions of EE. Previous studies have explored the use of the ankle site in adults (Heil, 2006; Hibbing et al, 2017; Kim et al, 2014; Leenders et al, 2003; Melanson & Freedson, 1995) and youth (de Vries et al, 2011; Hager et al, 2015; Heil, 2006) and have shown conflicting results. de Vries et al (2011), using the ActiGraph accelerometer, showed that the hip, compared to the ankle, was more accurate for predicting PA type using artificial neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, NHANES 2003–2006, which used a hip worn accelerometer, had valid data across the same age range in 618 of 987 participants (62.6%), and on average had 61.8 fewer minutes of waking wear time than U.S. ISCOLE participants (Tudor-Locke et al, 2015). Hager and colleagues (Hager et al, 2015) used an ankle-worn Actical accelerometer for a 7-day free-living measurement in adolescent girls, using a 24-hr wear protocol and showed the Actical device to be valid, reliable, and feasible for use on the ankle in adolescent females. Of primary importance was that during the 7-day free-living measurement, 99.6% of the 459 eligible participants agreed to wear the Actical and 386 (84.1%) had valid data at the end of the 7-day measurement, with an average wear time of approximately 1437 min/d.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of the means and standard deviations of the activity counts by intensity were examined graphically to identify clusters for each activity level [45]. Three researchers with accelerometry experience agreed upon thresholds for sedentary/light and light/MVPA to be tested.…”
Section: Methodsmentioning
confidence: 99%
“…First and last days, and days with incomplete 24-hour data were removed. Validated Actical ankle accelerometry thresholds for moderate/ vigorous physical activity (MVPA) 25 were applied, yielding MVPA (minutes/day).…”
Section: Moderate/vigorous Physical Activitymentioning
confidence: 99%